Bases informacionais para o desenvolvimento: as contradições na economia e as alternativas atuais - Oliveira, Felipe Morais de (2017)
The informational bases for development influence decision makers at different levels of society, especially in Public Management. These bases are constituted essentially by theoretical concepts and systems of indicators that indicate the direction for development. Thus, this dissertation aimed to analyze some of the main informational bases for development present in the current debate, through the analysis of the literature on the topic and empirical case studies. Despite the diversity of approaches to the concept of development, when analyzing the literature on the subject, one can notice a convergence in defining the ultimate goals: an increase in the quality of life in society. Therefore, there is a complexity inherent to this concept, given the multiplicity of factors that are involved in this process. However, historically in the economic science theoretical constructions, especially the Neoclassical School, this complexity has been replaced by a reductionism in the ways of analyzing development. It resulted in an narrow economistic point of view, based on contradictory concepts and the misuse of some indicators. These misuses and contradictions are evident, especially in the definition of economic growth, measured mainly by GDP, as the only factor considered to achieve development. In response to these contradictions, new approaches to the concept of development have emerged, systematizing all the complexity present in this subject, as presented by authors such as Amartya Sen and Ignacy Sachs, as well as international organizations, as in the case of United Nations ODSs. This structuration has motivated new ways of measuring development, therefore generating new informational bases, influencing decision makers and the whole society. Hence, this work’s general hypothesis is that there are a new set of informational bases that has a more efficient approach towards development, overcoming the contradictions presented in economic science. As a result, it was concluded that these new bases promote a holistic view on development, considering its objectives directly. Moreover, these new informational bases have the potential of being tools for promoting public dialogue, with a more participatory, democratic, holistic and effective decision-making process in society